“There wasn’t a guidebook for this”: caring leadership during crisis - Steilen, Kate; Stone-Johnson, Corrie (Frontiers in Education, 2023)
In this study, we seek to add to the descriptive literature on caring leadership through an examination of the work principals did to guide school communities through the COVID-19 pandemic in its earliest days. In this time, one essential role they played was as “caretaker for all;” not simply deciding, advising, or providing resources but responding with advocacy and compassion (Anderson et al., 2020). Even so, they simultaneously had to consider traditional instructional leadership expectations including teacher observation and supervision as well as student evaluation. This study examines the acts and expressions of caring leadership. Our research responds to one overarching question: What does caring leadership look like in action? Through close examination of seventeen elementary principals’ recollections of work during the school closures of 2020, this study highlights the elements of their decisions and choices that embodied caring leadership as well as demonstrates how these moves both incorporated and exceeded traditional leadership work. Our findings highlight the centrality of caring leadership not merely as part of leaders’ work, but as the actual work itself. We extend a presumed tautology of caring leadership to explicate the discrete tasks undertaken by caring leaders to sustain the work of schools.